Ayurvedic Pre-Conceptional Management in Patient with History of Abnormal Karyotype in Foetus - A Case Report (International Journal of Ayurveda and Pharma Research, 2021)
Every year worldwide, congenital anomalies contribute to the estimated amount of 2,95000 newborn deaths within 28 days of birth. Congenital anomalies result from many causes; one or more genetic or chromosomal defects, infections, nutritional or environmental terratogenic factors etc. May result in pregnancy loss, even if the foetus survives it will present with severe multi system organ damages, leading to lifelong disability and poor quality of life for both self and families which has got rippling impacts on the health care system and society. In Genetic defects involving karyotype errors allopathic treatment modalities are effective in some cases but only to a limited extent. In 2019 September, a 25 yr old female with history of medical termination of pregnancy (G1) approached OPD of Dept of Prasutitantra and Streeroga at Govt. Ayurveda college Women & Children Hospital. MTP was done at 12 wks of gestation due to gross foetal anomaly. Foetus was suspected to have hydrops foetalis as per the USG scan. Later karyotyping of the aborted foetus showed sex chromosome anomaly 45XO. She wanted to conceive again but was worried about the recurrence of karyotype error. She came to know about the concept of Sreyasi praja. She was willing to explore possibilities of Ayurvedic treatment modalities as pre conceptional care. After detailed case taking, analysing reports from the previous pregnancy, Ayurvedic treatment modalities including Sodhana therapies, Pumsavana vidhi for Garbha sthapanam, diet and regimen based on the fundamental principles were decided. And Soon after the treatment period patient got conceived in the month of February 2020 and the pregnancy was closely monitored and completed term uneventfully and delivered (FTND with RMLE) a healthy female baby with 2.6kg weight with APGAR 9 at 1 minute. The baby is growing up with normal IQ, active for her age and healthy. This case presents the effectiveness of Ayurvedic preconceptional management in achieving Sreyasi praja.